ANALISIS UTILITARIANISME TERHADAP DISPENSASI NIKAH PADA UNDANG-UNDANG PERKAWINAN NOMOR 1 TAHUN 1974 - Rifqi, Muhammad Jazil (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2017)
This study examine philosophically of foundation and requirements of marriage Act in Indonesia where one of them is 19year old for men and 16year old for women. However, when one of married people has not fulfilled the matter of age to marry, their parents have to submit marriage dispensation to the religious court so that their child is be able to continue his/her marriage that having been refused by KUA before. From this result of research, KUA Kotagede in 2015 has married three couples in which they have no standar age to marriage. Several decisions considering dispensation of marriage in religious court in 2015 have also indicated that majority of marriage childs who married under standart of age having been pregnant before they make agreement about marriage. Therefore, to analize dualism of law on the constitution of utilitarianism will be used which in briefly the conclusion of which suggests to make punishment that hoped reducing rate a marriage under established age.[Tulisan ini menelaah secara filosofis pondasi dan persyaratan usia pernikahan yang mana untuk laki-laki berusia 19 tahun dan perempuan berusia 16 tahun. Oleh karena itu, jika calon pengantin tidak memenuhi syarat tersebut maka orang tua mereka harus mengajukan dispensasi ke KUA setempat. Berdasarkan pada kasus yang terjadi di KUA Kotagede tahun 2015, terdapat tiga pernikahan yang syarat umurnya kurang. Kebanyakan dari mereka adalah yang hamil lebih dulu. Maka dari itu, analisis dualisme hukum dalam aturan utilitarianisme dapat digunakan untuk menyimpulkan secara ringkas yang mana disarankan untuk memberikan hukuman agar mengurangi tingkat pernikahan dini.]